Atorvastatin Upregulates microRNA-186 and Inhibits the TLR4-Mediated MAPKs/NF-κB Pathway to Relieve Steroid-Induced Avascular Necrosis of the Femoral Head - Zhang, Yusong; Ma, Limin; Lu, Erhai; Huang, Wenhua (Frontiers in Pharmacology, 2021)
Steroid-induced avascular necrosis of the femoral head (SANFH) is caused by the death of active components of femoral head owing to over doses of hormones. The use of lipid-lowering drugs to prevent SANFH in animals inspired us to identify the mechanisms involving Atorvastatin (Ato) in SANFH. However, it is still not well understood about how and to what extent Ato affects SANFH. This study aimed to figure out the efficacy of Ato in SANFH and the underlying molecular mechanisms. After establishment of SANFH model, histological evaluation, lipid metabolism, inflammatory cytokines, oxidative stress, apoptosis and autophagy of femoral head were evaluated. The differentially expressed microRNAs (miRs) after Ato treatment were screened out using microarray analysis. The downstream gene and pathway of miR-186 were predicted and their involvement in SANFH rats was analyzed. OB-6 cells were selected to simulate SANFH in vitro. Cell viability, cell damage, inflammation responses, apoptosis, and autophagy were assessed. Ato alleviated SANFH, inhibited apoptosis and promoted autophagy. miR-186 was significantly upregulated after Ato treatment. miR-186 targeted TLR4 and inactivated the MAPKs/NF-κB pathway. Inhibition of miR-186 reversed the protection of Ato on SANFH rats, while inhibition of TLR4 restored the protective effect of Ato. Ato reduced apoptosis and promoted autophagy of OB-6 cells by upregulating miR-186 and inhibiting the TLR4/MAPKs/NF-κB pathway. In conclusion, Ato reduced apoptosis and promoted autophagy, thus alleviating SANFH via miR-186 and TLR4-mediated MAPKs/NF-κB pathway.